A new mechanism for purchasing through personal interactions: fairness, trust and social influence in online group buying - Hung, Shiu-Wan; Cheng, Min-Jhih; Lee, Chia-Jung (Information technology & people (West Linn, Or.), 2022)
PurposeThe purpose of this article was to explore the influence of individual perception and social climate on consumer-initiated group-buying purchase decisions. An extended cross-level research model was used to explain how a new mechanism for purchasing through personal interactions could work.Design/methodology/approachThis study utilised a questionnaire survey for data gathering. The subjects of the investigation were group-buying initiators. Hierarchical linear modelling (HLM) was used to experimentally examine the research hypotheses.FindingsThe empirical results of the study indicate that the social influence of critical mass can effectively promote positive attitudes and intentions towards consumer-initiated online group buying. An individuals' perception of an initiator's fairness influences their trust in the initiator. In addition, trust in the initiator can positively and significantly influence buyers' attitudes and intentions to online group buying.Originality/valueMost previous studies on online group-buying focus on how social media influences group-buying behaviours. This study extends social media research by introducing an extended cross-level model to provide a comprehensive investigation into online-shopping. It is a preliminary attempt to systematically verify relationships at the individual and aggregate levels. The decision to group buying requires a relationship of trust to be formed before any transaction takes place, thereby increasing the intention to make a purchase. As a result, group buying is perceived as positive when interpersonal communication is very efficient, or when social influence is high.